EXPLORING THE INFLUENCE OF A TRIBAL ART WORKSHOP ON THE CREATIVE GROWTH OF DESIGN STUDENTS: A CASE STUDY AT AMITY SCHOOL OF FASHION DESIGN & TECHNOLOGY, AMITY UNIVERSITY GWALIOR, MADHYA PRADESH, INDIA, IN ALIGNMENT WITH NEP2020 - Rastogi, Twinkle; Devi, Salam Manisana; Singh, Tanu; Munjal, Kalpana; Thakuriya, Kajal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the ever-evolving landscape of modern higher education, the fusion of academic exploration with market dynamics emphasizes the inherent value of foundational craft principles. This synergy is particularly evident in specialized fields such as artisanal crafts, where individuals engage in a unique learning environment to enhance their proficiency and skills. Craft workshops, universally recognized as a critical priority, go beyond traditional teaching methods, serving as essential platforms for participants to not only grasp theoretical concepts but also apply them in practical, industry-relevant settings. The transformative impact of such craft workshops is significant, effectively bridging the gap between academic knowledge and real-world craft scenarios. This research article explores the transformative influence of a one-day Tribal Art & Sketching Workshop held at Amity School of Fashion Design & Technology (ASFDT), Amity University Madhya Pradesh (AUMP), on December 12, 2023. Led by the renowned artist Mr. Aalok Sharma, a national painting and sculpture artist and former fine art educator at Scindia Kanya Vidhyalaya, Gwalior, the workshop aimed to familiarize design students with the rich cultural heritage of Madhya Pradesh folk art, with a specific focus on Gond Art. Through a thorough analysis of the workshop's structure, participant engagement, and outcomes, this study aims to uncover the profound impact of the Indian art experience on the creative development of design students. The research methodology employs a combination of qualitative and quantitative approaches, aligning with the principles of the National Education Policy (NEP) 2020. This includes the use of a 5-point Likert scale for data collection to meticulously analyze the objectives, outcomes, and feedback from design students actively participating in the workshop. The results highlight a significant gap in traditional fashion design education that dynamic learning experiences like these seamlessly fill. By equipping students with practical skills and insights, the findings underscore the symbiotic relationship between workshops and holistic learning, aligning with NEP 2020's emphasis on experiential and multidisciplinary education. The resounding endorsement from students further supports the crucial role of workshops in enhancing their educational journey and aligns with NEP 2020's vision for learner-centric education. In essence, this study contributes to narrowing the theoretical-practical divide that often impedes comprehensive education. It emphasizes the transformative potential of workshops, redefining their status from peripheral add-ons to integral components of the educational framework. By showcasing the case of Amity School of Fashion Design and Technology in Amity University Gwalior, Madhya Pradesh, the study provides a model for educational institutions worldwide to incorporate innovation, relevance, and efficacy into their curriculum through the strategic integration of workshops in the craft sector, aligning with the progressive vision outlined in NEP 2020. (National Education Policy 2020).